Segurança alimentar e nutricional em comunidades quilombolas no Brasil – uma revisão da literatura. - LIMA, Giovana Dias (2023)
The present research work aims to present a study on food and nutrition security in quilombola communities in Brazil in the last five years. Law No. 11,346, of September 15, 2016, establishes that the public power must respect, protect, promote, inform and evaluate the effectiveness of the Human Right to Adequate Food. However, quilombolas are vulnerable and suffer discrimination from the institution. A survey of articles from the last five years on food and nutrition security in quilombola communities in Brazil was carried out. This is a systematic review of the literature with qualitative analysis, in which full articles were published in the years 2016 to 2021. The collection of information was carried out during the months of October and November 2021. In relation to quilombola food agriculture, it was observed that if few local people produce, as there is a rural exodus, which promotes failures in the local food supply. It reduced the consumption of in natura and minimally processed foods and increased the consumption of processed and ultraprocessed foods. It was observed that the quilombola population consumes less fish than beef, due to the pollution of the rivers and the practice of hunting, which is common in the quilombola population. Most of the quilombola population lives in food insecurity, due to socioeconomic and environmental aspects, this is observed in all age groups. Studies show that it is four times larger than the average population. A high prevalence of food insecurity was observed in this population, as well as a lack of intake of certain foods, such as fruits and vegetables. In addition, the absence of running water, other than sewage, per capita income and access to health services exacerbate the situation. Based on the information obtained, a reflection was carried out on food insecurity in quilombola communities, making explicit the neglect of the public power and that urgent measures must be adopted with a special and fairer attention to this people who have suffered so much and who fight for the right that should be common to all Brazilians without distinction.